PENERAPAN KEGIATAN NUMERASI DI SEKOLAH DASAR : ANALISIS MEDIA YANG MEMBERI PENGARUH PADA KETERAMPILAN NUMERASI DAN CAPAIAN BELAJAR SISWA - Rosalia Eka Lusiana; Sumarno; Ida Dwijayanti (STKIP Subang, 2024)
Numeracy skills are very important to be given to elementary school children because they can influence student learning outcomes by utilizing appropriate, creative and innovative learning media. This study aims to examine the variety of use of learning media that influence numeracy skills and student learning outcomes in several public and private elementary schools in Semarang City. The research method used by the researcher is qualitative description. The subjects of the study were twenty-nine teachers from four public and six private schools in Semarang City. Data collection techniques in the form of questionnaires and interviews. Data collection instruments in the form of questions are the application of numeracy that has been done, learning methods applied, learning media used, teacher perspectives on numeracy that affect student learning outcomes and numeracy skills. The results showed that the application of numeracy learning that was carried out correctly and accordingly by 20% and 80% was not appropriate. The learning methods used are very varied, 42% of teachers use contextual, other methods are in the form of games, cooperative, PJBL and PBL. Learning media that are widely used by teachers are concrete objects by 47%, the use of other media is in the form of games and ICT. The perspective of teachers on numeracy shows that 76% of teachers do not understand numeracy well and only 24% of teachers understand it well. This affects student learning achievement, namely 52% of students are still not good results and there are 65% of students whose numeracy skills are not as they should. The researcher suggested to the next researcher to more comprehensively examine the analysis of the use of effective learning media in order to influence the learning outcomes and numeracy skills of elementary school students to increase according to development and needs.